Nano-porous CoFeS2 / Fe0. 95S1.05 composite electrocatalyst as well as preparation method and application thereof
Through the preparation of nanoporous CoFeS2/Fe0.95S1.05 composite electrocatalyst, the use of solvent heat and one-step vulcanization technology, the problem of slow reaction kinetics and low selectivity in the electrocatalytic nitrate reduction ammonia production technology was solved, and high ammonia was achieved The effect of yield and high Faraday efficiency.
Patent Information
- Application Number
- CN202411349516.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-17
AI Technical Summary
The existing electrocatalytic nitrate reduction ammonia production technology has problems such as slow reaction kinetics, low selectivity and low Faraday efficiency, and the electrochemical reduction performance of CoS2 nitrates reported earlier is poor.
Nanoporous CoFeS2/Fe0.95S1.05 composite electrocatalyst is prepared by solvent heat and one-step vulcanization, and the catalytic performance is improved by using the synergistic effect and porous structure of bimetallic sulfides.
High ammonia yield, high Faraday efficiency and high cycling stability are achieved, the problem of bimetallic sulfur bond failure caused by mechanical mixing is avoided, and the electrochemical activity and electrical conductivity of the catalyst is significantly improved.
Smart Images

Figure CN119320960A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalysts for electrocatalytic nitrate reduction to synthesize ammonia, and in particular to a nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalyst and its preparation method and application. Background Art
[0002] Ammonia (NH3) is an indispensable raw material in chemical and agricultural production, and is also regarded as a promising hydrogen storage medium and carbon-free energy carrier. At present, NH3 is mainly produced by the energy-intensive Haber-Bosch process, which has high energy consumption, high CO2 greenhouse gas emissions and harsh operating conditions. In recent years, electrocatalytic nitrate reduction to ammonia (NRA) under ambient conditions has become a promising, green and sustainable method to produce NH3 at room temperature and pressure. Nitrate is one of the main environmental pollutants and is widely present in industrial wastewater and domestic sewage. It seriously endangers human health and the ecological environment. Therefore, NRA not only realizes the production of ammonia, but also realizes environmental remediation. However, NRA is a complex multi-electron process involving the transfer of 9 protons and 8 electrons. This makes the NRA reaction kinetics slow and produces various nitrogen-containing intermediates, such as N2, NO2 - , N2H4, etc. In addition, NO3 - The potential of the reaction to NH3 is usually lower than that of the electrocatalyst hydrogen evolution reaction (HER), resulting in H2 production, which reduces selectivity and Faradaic efficiency (FE). Therefore, a highly selective and active catalyst is needed to effectively and selectively convert NO3 - Converted to NH3.
[0003] Transition metal compounds have been identified as being able to activate and electrochemically reduce NO3 - Among them, metal sulfides are promising in catalyzing NRA due to their semi-metallic properties that can improve the reaction kinetics and their high water dissociation ability to provide sufficient proton source. However, the performance of the electrochemical reduction reaction of nitrate ion in CoS2 reported earlier is still far below a satisfactory level.
[0004] Metal-organic frameworks (MOFs) are considered to be suitable support materials for the field of electrocatalysis due to their ordered crystallinity, porous structure, and high specific surface area. First, their variable metal nodes provide the possibility for the introduction of bimetallics. Second, calcination can easily evolve from a porous framework into a graded metal@C structure, which can provide a good environment for electron transfer. The porous structure enables the material to fully contact the electrolyte interface and is conducive to maintaining the stability of the structure. Obviously, metal sulfide composites prepared by in-situ calcination of metal MOFs and sulfur can effectively combine the advantages of MOFs and metal sulfides.
[0005] Therefore, the present invention provides a nanoporous CoFeS2 / Fe 0.95 S 1.05 The composite electrocatalyst is used as a NRA catalyst and as a NRA cathode material to solve the above problems. Summary of the invention
[0006] Based on the above, the object of the present invention is to provide a nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalyst and its preparation method and application, preparation of a nanoporous CoFeS2 / Fe with simple process, low cost, high conductivity and high catalytic performance 0.95 S 1.05 Composite electrocatalysts achieve high ammonia yield and high FE while improving the cycle stability of the catalyst itself.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A nanoporous CoFeS2 / Fe 0.95 S 1.05 The preparation method of the composite electrocatalyst comprises the following steps:
[0009] DMF, anhydrous ethanol and deionized water are used as a mixed solvent, cobalt salt, iron salt and organic ligand are added, and stirred to fully dissolve them to obtain a mixed solution;
[0010] The mixed solution is subjected to a solvothermal reaction to obtain a MOF-74 precursor;
[0011] The MOF-74 precursor is subjected to one-step sulfurization to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0012] A nanoporous CoFeS2 / Fe 0.95 S 1.05 A preferred embodiment of the method for preparing the composite electrocatalyst is that the volume ratio of the DMF, the anhydrous ethanol and the deionized water is 1:(1-5):(1-5); and the mass ratio of the cobalt salt, the iron salt and the organic ligand is (1.7-4):(1.2-2.8):1.
[0013] A nanoporous CoFeS2 / Fe 0.95 S 1.05 In a preferred embodiment of the method for preparing the composite electrocatalyst, the molar concentration of the cobalt salt in the mixed solvent is 0.02 to 0.04 mol / L.
[0014] A nanoporous CoFeS2 / Fe0.95 S 1.05 A preferred embodiment of the method for preparing the composite electrocatalyst, wherein the cobalt salt comprises cobalt nitrate hexahydrate; the iron salt comprises ferrous chloride tetrahydrate; and the organic ligand comprises H4DOBDC.
[0015] A nanoporous CoFeS2 / Fe 0.95 S 1.05 According to a preferred embodiment of the method for preparing the composite electrocatalyst, when the cobalt salt, the iron salt and the organic ligand are added to the mixed solvent and stirred, the stirring temperature is room temperature and the stirring time is 1 to 6 hours.
[0016] A nanoporous CoFeS2 / Fe 0.95 S 1.05 According to a preferred embodiment of the method for preparing the composite electrocatalyst, during the solvent thermal reaction, the reaction temperature is 100 to 180° C. and the reaction time is 12 to 30 hours.
[0017] A nanoporous CoFeS2 / Fe 0.95 S 1.05 The preferred embodiment of the preparation method of the composite electrocatalyst is that the sulfurization process is carried out in an argon atmosphere, the temperature is 600-700°C, the heating rate is 2-5°C / min, and the insulation time is 1-4h.
[0018] A nanoporous CoFeS2 / Fe 0.95 S 1.05 A preferred embodiment of the method for preparing the composite electrocatalyst is that in the sulfurization process, sublimated sulfur powder is used for sulfurization, and the mass ratio of the sublimated sulfur powder to the MOF-74 precursor is (2-5):1.
[0019] A nanoporous CoFeS2 / Fe 0.95 S 1.05 The composite electrocatalyst is prepared by any one of the preparation methods described above.
[0020] A nanoporous CoFeS2 / Fe 0.95 S 1.05 Application of composite electrocatalysts based on the above nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalyst, the nanoporous CoFeS2 / Fe 0.95 S 1.05 The composite electrocatalysts were used as NRA cathode materials.
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a nanoporous CoFeS2 / Fe 0.95 S 1.05The composite electrocatalyst and its preparation method and application have the advantages of simple process, short preparation cycle and low cost. CoFeS2 / Fe prepared by solvent thermal and one-step sulfurization 0.95 S 1.05 The composite material has the advantages of high reduction-oxidation activity and high conductivity. At the same time, it can also avoid the mechanical mixing of bimetallic materials and prevent the lack of bimetallic sulfur bonds after mechanical mixing of FeS and CoS, which makes it impossible to reflect the synergistic effect and hinders the catalytic performance.
[0023] Nanoporous CoFeS2 / Fe prepared by the invention 0.95 S 1.05 The composite electrocatalyst exhibits excellent electrochemical performance when used as NRA cathode material. First, the bimetallic sulfide has excellent electrical conductivity, which is conducive to rapid electron conduction; second, the effective bimetallic synergistic effect can provide high redox activity; finally, the nanoporous CoFeS2 / Fe 0.95 S 1.05 The porous structure of the composite electrocatalyst makes it have a high electrochemical active area (13.47 cm ECSA 2 ), and the loose porous structure enables the negative electrode material to fully contact the electrolyte interface and is conducive to maintaining the stability of the structure. 0.95 S 1.05 When the composite electrocatalyst is used as NRA cathode material, it exhibits excellent properties such as high ammonia yield, high FE and high durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0025] Figure 1 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 SEM morphology of
[0026] Figure 2 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 Energy dispersive X-ray spectroscopy (EDS)-Mapping diagram;
[0027] Figure 3 The CoFeS2 / Fe prepared in Example 1 0.95 S1.05 X-ray photoelectron spectroscopy (XPS);
[0028] Figure 4 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - - Ammonia yield and FE in N solution;
[0029] Figure 5 The CoFeS2 / Fe prepared in Example 2 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - - Ammonia yield and FE in N solution;
[0030] Figure 6 The CoFeS2 / Fe prepared in Example 3 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - - Ammonia yield and FE in N solution;
[0031] Figure 7 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - - Cyclic stability test results in N solution;
[0032] Figure 8 The CoFeS2 / Fe prepared in Example 4 0.95 S 1.05 SEM morphology of
[0033] Fig. 9 The CoS / Co9S8 prepared in Comparative Example 1 was used as the working electrode in 0.1M Na2SO4+200ppm NO3 - - Ammonia yield and FE in N solution;
[0034] Fig.10 The FeS prepared in Comparative Example 2 was used as the working electrode in 0.1M Na2SO4+200ppm NO3 - - Ammonia yield and FE in N solution;
[0035] Fig.11 This is the SEM morphology of Co9S8 / FeS prepared in comparative example 3. DETAILED DESCRIPTION
[0036] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0037] The present invention provides a nanoporous CoFeS2 / Fe 0.95 S 1.05 The preparation method of the composite electrocatalyst comprises the following steps:
[0038] S100: DMF, anhydrous ethanol and deionized water are used as a mixed solvent, and cobalt salt, iron salt and organic ligand are added, and stirred to fully dissolve them to obtain a mixed solution;
[0039] Specifically, the mass ratio of cobalt salt, iron salt and organic ligand is (1.7-4):(1.2-2.8):1; the volume ratio of DMF, anhydrous ethanol and deionized water is 1:(1-5):(1-5); the molar concentration of cobalt salt in the mixed solvent is 0.02-0.04 mol / L; the cobalt salt includes cobalt nitrate hexahydrate; the iron salt includes ferrous chloride tetrahydrate; the organic ligand includes H4DOBDC; during the stirring process, the stirring temperature is room temperature and the stirring time is 1-6 hours.
[0040] S200: subjecting the mixed solution to a solvothermal reaction to obtain a MOF-74 precursor;
[0041] Specifically, during the solvent thermal reaction, the reaction temperature is 100 to 180° C., and the reaction time is 12 to 30 hours.
[0042] S300: One-step sulfurization of MOF-74 precursor to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0043] Specifically, the vulcanization process is carried out in an argon atmosphere, the temperature is 600-700°C, the heating rate is 2-5°C / min, and the insulation time is 1-4h; sublimated sulfur powder is used, and the mass ratio of the sublimated sulfur powder to the MOF-74 precursor is (2-5):1; wherein, during the vulcanization process, the sublimated sulfur powder is placed in front of the MOF-74 precursor, and since the argon gas flow flows from one side of the sublimated sulfur powder to the MOF-74 precursor, the sublimated sulfur powder and the MOF-74 precursor are fully reacted.
[0044] The present invention will be further described below by means of specific examples.
[0045] Example 1
[0046] A nanoporous CoFeS2 / Fe 0.95 S 1.05 Preparation method of composite electrocatalyst:
[0047] S100: Weigh 0.204 g of cobalt nitrate hexahydrate, 0.06 g of ferrous chloride tetrahydrate, and 50 mg of H4DOBDC and dissolve them in a mixed solvent of DMF, anhydrous ethanol, and deionized water with a total volume of 18 ml, wherein the volume ratio of DMF, anhydrous ethanol, and deionized water is 1:1:1, and stir continuously at room temperature for 5 h to obtain a mixed solution.
[0048] S200: subjecting the mixed solution to a solvothermal reaction at a temperature of 120° C. for 24 h to obtain MOF-74 black powder.
[0049] S300: The MOF-74 black powder was subjected to a one-step sulfurization treatment. The mass ratio of sulfur powder to MOF-74 precursor was 5:1. The sulfurization process was carried out in an argon atmosphere at a temperature of 700 °C, a heating rate of 5 °C / min, and a holding time of 2 h to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0050] Composite electrocatalysts used as NRA cathode materials for NO3 reduction - , based on CoFeS2 / Fe 0.95 S 1.05 The electrochemical performance test was carried out in an H-type electrolytic cell with Ag / AgCl as the working electrode, platinum wire as the reference electrode and platinum wire as the counter electrode.
[0051] Example 2
[0052] A nanoporous CoFeS2 / Fe 0.95 S 1.05 Preparation method of composite electrocatalyst:
[0053] S100: Weigh 0.1455 g of cobalt nitrate hexahydrate, 0.099 g of ferrous chloride tetrahydrate, and 50 mg of H4DOBDC and dissolve them in a mixed solvent of DMF, anhydrous ethanol, and deionized water with a total volume of 18 ml, wherein the volume ratio of DMF, anhydrous ethanol, and deionized water is 1:5:5, and stir continuously at room temperature for 6 hours to obtain a mixed solution.
[0054] S200: subjecting the mixed solution to a solvothermal reaction at a temperature of 180° C. for 30 h to obtain MOF-74 black powder.
[0055] S300: The MOF-74 black powder was subjected to a one-step sulfurization treatment. The mass ratio of sulfur powder to MOF-74 precursor was 2:1. The sulfurization process was carried out in an argon atmosphere at a temperature of 700 °C, a heating rate of 2 °C / min, and a holding time of 4 h to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0056] Composite electrocatalysts used as NRA cathode materials for NO3 reduction - , based on CoFeS2 / Fe 0.95 S 1.05 The electrochemical performance test was carried out in an H-type electrolytic cell with Ag / AgCl as the working electrode, platinum wire as the reference electrode and platinum wire as the counter electrode.
[0057] Example 3
[0058] A nanoporous CoFeS2 / Fe 0.95 S 1.05 Preparation method of composite electrocatalyst:
[0059] S100: Weigh 0.087 g of cobalt nitrate hexahydrate, 0.139 g of ferrous chloride tetrahydrate, and 50 mg of H4DOBDC and dissolve them in a mixed solvent of DMF, anhydrous ethanol, and deionized water with a total volume of 18 ml, wherein the volume ratio of DMF, anhydrous ethanol, and deionized water is 1:3:3, and stir continuously at room temperature for 3 h to obtain a mixed solution.
[0060] S200: subjecting the mixed solution to a solvothermal reaction at a temperature of 100° C. for 12 h to obtain MOF-74 black powder.
[0061] S300: The MOF-74 black powder was subjected to a one-step sulfurization treatment. The mass ratio of sulfur powder to MOF-74 precursor was 4:1. The sulfurization process was carried out in an argon atmosphere at a temperature of 700°C, a heating rate of 3°C / min, and a holding time of 1h to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0062] Composite electrocatalysts used as NRA cathode materials for NO3 reduction - , based on CoFeS2 / Fe 0.95 S 1.05 The electrochemical performance test was carried out in an H-type electrolytic cell with Ag / AgCl as the working electrode, platinum wire as the reference electrode and platinum wire as the counter electrode.
[0063] Example 4
[0064] The preparation process is basically the same as that of Example 1, wherein the sulfurization temperature is 600°C (in other embodiments, the sulfurization temperature can be set to 650°C), and nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
[0065] In order to further illustrate the key points of this patent, a comparative case is added for illustration.
[0066] Comparative Example 1
[0067] The preparation process is basically the same as that of Example 1, wherein ferrous chloride tetrahydrate is not added for reaction, and the final product obtained is CoS / Co9S8.
[0068] Comparative Example 2
[0069] The preparation process is basically the same as that of Example 1, wherein cobalt nitrate hexahydrate is not added for reaction, and the final product obtained is FeS.
[0070] Comparative Example 3
[0071] The preparation process was basically the same as that of Example 1, wherein the sulfurization temperature was 800°C, and a nanoporous Co9S8 / FeS composite electrocatalyst was prepared.
[0072] Nanoporous CoFeS2 / Fe prepared in Examples 1-4 0.95 S 1.05 When the composite electrocatalyst is used as NRA cathode material, it has excellent electrochemical performance. Figure 1-8 shown.
[0073] Figure 1 The nanoporous CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 From the SEM morphology of the composite electrocatalyst, it can be seen that CoFeS2 / Fe0.95S1.05 has a loose porous structure, the particles are evenly dispersed, the catalyst and the electrolyte interface can be fully in contact and it is conducive to maintaining the stability of the structure and achieving rapid electron conduction.
[0074] Figure 2 The nanoporous CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 The energy dispersive X-ray spectroscopy (EDS)-Mapping diagram of the composite electrocatalyst shows that the composite material mainly contains five elements: C, O, Fe, Co, and S, with their mass percentages being 15.2%, 19%, 25.7%, 21.4%, and 18.6%, respectively, and the five elements are evenly distributed in the prepared catalyst.
[0075] Figure 3 The nanoporous CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 The XPS full spectrum and high-resolution spectrum of the composite electrocatalyst, where (a) the XPS full spectrum, (b) Co 2p, (c) Fe 2p, and (d) S2p are high-resolution spectra. Figure 3 a It can be seen that CoFeS2 / Fe 0.95 S 1.05 The composite material contains five elements: C, O, Fe, Co, and S. The O element mainly comes from the water molecules in the air oxidized and adsorbed on the sample surface. The high-resolution spectrum of Co 2p ( Figure 3 b) The peaks at 781.3 and 797.2 eV can be attributed to Co 2+ Characteristics of 2p 3 / 2 and 2p 1 / 2 , while the peaks at 778.2 and 793.5 eV belong to Co 0 At the same time, 2p at 786.9 and 802.7 eV were also observed. 3 / 2 and 2p 1 / 2 Satellite peaks further indicate that Co 0 and Co 2+ The characteristic peaks in the high-resolution spectrum of Fe 2p include: Fe 2+ (724.5eV and 710.9eV),Fe 3+ (714.2eV) and satellite peak (718.7eV) ( Figure 3 c). The multivalent states of these metals undoubtedly help promote fast redox reactions. For S2p spectra ( Figure 3 d), the peaks at 161.8 and 163.9 eV can be attributed to S2p 3 / 2 and S2p 1 / 2 , the peak located at 165.2 eV indicates the presence of typical metal-sulfur (MS) bonds in the material.
[0076] Figure 4 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - -N solution. As shown in the figure, the NH3 yield increases with the increase of negative potential, while its FE NH3 It exhibits a volcanic behavior, with the highest value reaching 94.79% at -1.0 V. The corresponding NH3 yield is 2.7055 mg h -1 mg cat . -1 , surpassing most existing NRA catalysts.
[0077] Figure 5 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - -N solution. As shown in the figure, the ammonia yield and FE have a similar change trend to that of Example 1, and the ammonia yield is slightly lower than that of Example 3, with a maximum ammonia yield of 2.96 mg h -1 mg cat . -1 .
[0078] Figure 6 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - -N solution. As shown in the figure, the ammonia yield and FE have a similar change trend to that of Example 1. The ammonia yield is slightly lower than that of Example 1, and the maximum ammonia yield is 3.18 mg h -1 mg cat . -1 .
[0079] Figure 7 The CoFeS2 / Fe prepared in Example 1 0.95 S 1.05 As working electrode in 0.1MNa2SO4+200ppmNO3 - -N solution. As shown in the figure, after 12 cycles, the fluctuations of NH3 yield and FE were within a reasonable range and did not decrease significantly. Therefore, under this experimental condition, CoFeS2 / Fe 0.95 S 1.05 The catalyst has high cyclic stability.
[0080] like Figure 8 As shown, the CoFeS2 / Fe prepared in Example 4 0.95 S 1.05 The SEM morphology of the electrode was compared with that of Example 1. The electrochemical active area was reduced, and the electron transfer rate was decreased, thereby slowing down the electrochemical redox reaction kinetics. - The maximum ammonia yield was 2.46 mg h in NRA reaction in N-N solution. -1 mg cat . -1 , FE shows a decrease with the increase of negative potential, and its maximum ammonia yield is slightly lower than that of CoFeS2 / Fe prepared in Example 1.0.95 S 1.05 , but still exceeds most existing NRA catalysts and has excellent catalytic performance.
[0081] The products prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3 were subjected to performance tests.
[0082] like Fig. 9 As shown, in Comparative Example 1, ferrous chloride tetrahydrate was not added to the reaction, and the prepared product was CoS / Co9S8, which was used as the NRA cathode material in 0.1M Na2SO4+200ppmNO3 - -N solution. It can be seen that the NH3 yield increases with the increase of negative potential, but the maximum is 1.63 mg h -1 mg cat . -1 The FE decreases with increasing negative potential, and it is obvious that single metal sulfides exhibit poor catalytic performance.
[0083] like Fig.10 As shown, in Comparative Example 2, no cobalt nitrate hexahydrate was added to react, and the product prepared was FeS, which was used as the NRA cathode material in 0.1M Na2SO4+200ppm NO3 - -N solution. It can be seen that the ammonia yield and FE have a similar change trend to CoS / Co9S8, the ammonia yield is slightly lower than CoS / Co9S8, but the FE drops sharply. The catalytic performance is significantly inferior to the test results of Example 1.
[0084] like Fig.11 As shown, compared with Example 1 and Example 4, the morphology of Co9S8 / FeS prepared in Comparative Example 3 has changed greatly, the particle size has become larger and the agglomeration phenomenon is obvious, resulting in a decrease in the electrochemical active area, a decrease in the electron transfer rate, and ammonia production rate cannot keep up with the charge consumption rate, resulting in a sharp decrease in FE. - The maximum ammonia yield was 1.28 mg h in NRA reaction in N-N solution. -1 mg cat . -1 , the catalytic performance is poor.
[0085] The electrochemical test results show that the nanoporous CoFeS2 / Fe 0.95 S 1.05 The composite electrocatalysts exhibited excellent electrochemical performance when used as NRA cathode materials.
[0086] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A nanoporous CoFeS2 / Fe 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: The following steps are involved: DMF, anhydrous ethanol and deionized water are used as a mixed solvent, cobalt salt, iron salt and organic ligand are added, and stirred to fully dissolve to obtain a mixed solution; The mixed solution is subjected to a solvothermal reaction to obtain a MOF-74 precursor; The MOF-74 precursor is subjected to one-step sulfurization to obtain nanoporous CoFeS2 / Fe 0.95 S 1.05 Composite electrocatalysts.
2. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: The volume ratio of the DMF, the anhydrous ethanol and the deionized water is 1:(1-5):(1-5); the mass ratio of the cobalt salt, the iron salt and the organic ligand is (1.7-4):(1.2-2.8):
1.
3. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: The molar concentration of the cobalt salt in the mixed solvent is 0.02-0.04 mol / L.
4. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: The cobalt salt includes cobalt nitrate hexahydrate; the iron salt includes ferrous chloride tetrahydrate; and the organic ligand includes H4DOBDC.
5. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: When the cobalt salt, the iron salt and the organic ligand are added to the mixed solvent and stirred, the stirring temperature is room temperature and the stirring time is 1 to 6 hours.
6. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: During the solvent thermal reaction, the reaction temperature is 100 to 180° C. and the reaction time is 12 to 30 hours.
7. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: The vulcanization process is carried out in an argon atmosphere, the temperature is 600-700° C., the heating rate is 2-5° C. / min, and the insulation time is 1-4 hours.
8. The nanoporous CoFeS2 / Fe according to claim 1 0.95 S 1.05 A method for preparing a composite electrocatalyst, characterized in that: During the vulcanization process, sublimated sulfur powder is used for vulcanization, and the mass ratio of the sublimated sulfur powder to the mass ratio of the MOF-74 precursor is (2-5):
1.
9. A nanoporous CoFeS2 / Fe 0.95 S 1.05 A composite electrocatalyst, characterized in that Prepared by the preparation method according to any one of claims 1 to 8.
10. A nanoporous CoFeS2 / Fe 0.95 S 1.05 Application of composite electrocatalyst based on the nanoporous CoFeS2 / Fe 0.95 S 1.05 A composite electrocatalyst, characterized in that The nanoporous CoFeS2 / Fe 0.95 S 1.05 The composite electrocatalysts were used as NRA cathode materials.